2003
DOI: 10.1128/jcm.41.2.552-557.2003
|View full text |Cite
|
Sign up to set email alerts
|

Highly Polymorphic Microsatellite for Identification of Candida albicans Strains

Abstract: The polymorphism of a new microsatellite locus (CAI) was investigated in a total of 114 Candida albicans strains, including 73 independent clinical isolates, multiple isolates from the same patient, isolates from several episodes of recurrent vulvovaginal infections, and two reference strains. PCR genotyping was performed automatically, using a fluorescence-labeled primer, and in the 73 independent isolates, 26 alleles and 44 different genotypes were identified, resulting in a discriminatory power of 0.97. CAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 35 publications
6
84
0
Order By: Relevance
“…To address this question, we used a molecular typing method based on four microsatellite markers separately shown to be suitable for epidemiological studies. 24,25 These markers are located on different chromosomes, are stable over many generations, and are highly discriminative. Bretagne et al observed a discriminatory power of 0.97 using a combination of the EF3, HIS3 and CDC3 microsatellites while Sampaio et al obtained a similar value using CAI alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this question, we used a molecular typing method based on four microsatellite markers separately shown to be suitable for epidemiological studies. 24,25 These markers are located on different chromosomes, are stable over many generations, and are highly discriminative. Bretagne et al observed a discriminatory power of 0.97 using a combination of the EF3, HIS3 and CDC3 microsatellites while Sampaio et al obtained a similar value using CAI alone.…”
Section: Discussionmentioning
confidence: 99%
“…23 Clones were genotyped using four microsatellite markers: one set of three loci referred to as EF3, CDC3, HIS3, located on chromosomes 5, 1 and 2, respectively, 24 and one additional marker referred to as CAI, located on chromosome 4. 25 Amplification reactions were performed using primer sequences and thermal cycling parameters described elsewhere. 24,25 Fragment size analysis of the polymerase chain reaction fragments was performed by automated fluorescent capillary electrophoresis as previously described.…”
Section: Genotyping Of C Albicans By the Analysis Of Microsatellite mentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods, such as electrophoretic karyotyping, restriction enzyme analysis, Southern blotting with probes, randomly amplified polymorphic DNA, and multilocus sequence typing (MLST), have been used to distinguish and type C. glabrata isolates (2,7,8,14,21,28). Microsatellite polymorphism analysis has been widely used for typing fungi (3,4,11,15,18,25), and this could be an alternative, easy-to-perform, reproducible method suitable for large-scale studies of C. glabrata epidemiology. Recently, Foulet et al described three polymorphic microsatellite markers to investigate the delineation of clinical C. glabrata isolates (12).…”
mentioning
confidence: 99%
“…The amplification of species-specific microsatellites by PCR has been successfully applied in molecular epidemiology and population studies to differentiate between C. albicans strains [8] [9]. The microsatellite loci CAI (CAA repeats), CAIII (GAA repeats), and CAVI (TAAA repeats) present in the C. albicans genome have been used for genotyping clinical isolates.…”
Section: Introductionmentioning
confidence: 99%